(untitled) (MAUSAM, 2001)
A mobile temperature survey of Brihan Mumbai (Greater Bombay) was undertaken on 16 January 1997 which incidentally turned out to be the coldest winter night. Heat islands were found well inside the city, away from the coastal boundary, within a distinct tongue of warm air splitting in three branches roughly along the three sub- urban railway tracks. The finding of the study were in sharp contrast with similar studies conducted during the early seventies by Daniel and Krishnamurthy (1973) and later by Mukherjee and Daniel (1976). They found a remarkable influence of sea on the horizontal temperature distribution in comparison to other factors of urbanisation and noticed the heat island over Malabar Hill, Girgaurn and Cuffe Parade area. The survey conducted after a span of twenty-two years, showed that the temperature distribution in the city and suburbs has been modified significantly and that the effect of urbanisation has overtaken the effect of maritime influence in the formation and maintenance of heat islands. Another mobile temperature survey was conducted during the early hours of 11 May 1997 on the same lines as survey conducted on 16 January 1997, to confirm the findings of earlier survey and to assess seasonal changes in the intensities of heat island. This later survey showed similar pattern of horizontal temperature distribution, though the intensity of heat island observed was only 5.5° C as compared to 11.8° C observed during winter.